Systemic upregulation of MTP2- and HMA2-mediated Zn partitioning to the shoot supplements local Zn deficiency responses - Sinclair, Scott; Senger, Toralf; Talke, Ina N.; Cobbett, Christopher S.; Haydon, Mike; Krämer, Ute (The plant cell, 2018)
Low bioavailable concentrations of the micronutrient zinc (Zn) limit agricultural production on 40% of cultivated land. Here, we demonstrate that plant acclimation to Zn deficiency involves systemic regulation. Physiological Zn deficiency of Arabidopsis thaliana shoots results in increased root transcript levels of the membrane transport protein-encoding genes METAL TRANSPORT PROTEIN2 (MTP2) and HEAVY METAL ATPASE2 (HMA2), which are unresponsive to the local Zn status of roots. MTP2 and HMA2 act additively in the partitioning of Zn from roots to shoots. Chimeric GFP fusion proteins of MTP2 complement an mtp2 mutant and localize in the endoplasmic reticulum (ER) membrane of the outer cell layers from elongation to root hair zone of lateral roots. MTP2 restores Zn tolerance in a hypersensitive yeast mutant. These results are consistent with cell-to-cell movement of Zn toward the root vasculature inside the ER-luminal continuum through the desmotubules of plasmodesmata, under Zn deficiency. The previously described Zn deficiency response comprises transcriptional activation of target genes, including ZINC-REGULATED TRANSPORTER IRON-REGULATED TRANSPORTER PROTEIN genes ZIP4 and ZIP9, by the F-group bZIP transcription factors bZIP19 and bZIP23. We show that ZIP4 and ZIP9 respond to the local Zn status in both roots and shoots, in contrast to the systemic regulation identified here. Our findings are relevant for crop management and improvement toward combating human nutritional Zn deficiency that affects 30 to 50% of the world’s population.